Case study: Dose response of caffeine on 20-km handcycling time trial performance in a paratriathlete - Graham-Paulson, T.; Perret, C.; Goosey-Tolfrey, V. (International Journal of Sport Nutrition and Exercise Metabolism, 2018)
Caffeine`s (CAF) ability to influence upper-body exercise endurance performance may be related to an individual`s training status. This case study therefore aimed to investigate the ergogenic effects of CAF dose on 20-km time trial (TT) performance of an elite male paratriathlete (wheelchair user; age = 46 years, body mass = 76.9 kg, body fat?=?25.4%, and handcycling [peak oxygen uptake, VO2peak]=3.45 L/min). The athlete completed four 20-km handcycling TTs on a Cyclus II ergometer under controlled laboratory conditions following the ingestion of 2, 4, and 6 mg/kg CAF or placebo (PLA). Blood lactate concentration, power output, arousal, and ratings of perceived exertion were recorded. Ingestion of 2, 4, and 6 mg/kg CAF resulted in a 2%, 1.5%, and 2.7% faster TT compared with PLA (37:40 min:s). The participant`s blood lactate concentration increased throughout all trials and was greater during CAF compared with PLA. There were no obvious differences in ratings of perceived exertion between trials despite different performance times. Baseline arousal scores differed between PLA and 4 mg/kg CAF (1 = low), and 2 and 6 mg/kg CAF (3 = moderate). Arousal increased at each time point following the ingestion of 4 and 6 mg/kg CAF. The largest CAF dose resulted in a positive pacing strategy, which, when combined with an end spurt, resulted in the fastest TT. CAF improved 20-km TT performance of an elite male paratriathlete, which may be related to greater arousal and an increased power output for a given rating of perceived exertion.